2.5k views
0 votes
Help me please!!!!!!

Help me please!!!!!!-example-1
User Kudu
by
5.6k points

1 Answer

2 votes

Answer:

c

Explanation:

Since the perimeters are equal, then equate the perimeter expressions, that is

4(x - 2) = 6(
(1)/(2) x + 5) ← distribute parenthesis on both sides

4x - 8 = 3x + 30 ( subtract 3x from both sides )

x - 8 = 30 ( add 8 to both sides )

x = 38

Substitute x = 38 into either of the 2 perimeter expressions

perimeter = 4(x - 2) = 4(38 - 2) = 4 × 36 = 144 in → c

User Plamen G
by
5.8k points